ANALYSIS OF PENDING BPJS CLAIMS ISSUES IN THE CASEMIX UNIT OF RS ISLAM MASYITHOH BANGIL 2025 - Junaedi Hasmi A; Rachmad Cahyadi; Mundakir Mundakir (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This study analyzes pending claims within the INA-CBG–based reimbursement process at the Casemix Unit of RS Islam Masyithoh Bangil in 2025. Under Indonesia’s National Health Insurance (JKN), claim submission functions as a critical interface between clinical services and financing governance; disruptions in this process may affect both operational workflows and hospital cash flow. This research employed a descriptive case study design using semi-structured interviews, non-participant observation, and document review. To strengthen the process-based analysis, the study incorporated descriptive quantitative tabulation of monthly verification documents from January–November 2025 at the claim level (unique SEP), covering claim status, service type, pending categories, and submitted value. The dataset recorded 5,272 claims, of which 2,417 were pending (45.8%), with a cumulative pending submission value of IDR 8,427,504,800 and marked month-to-month fluctuations. The composition of pending categories shifted across months, predominantly involving coding rules and service standards, while administrative completeness remained consistently present at a smaller proportion. These findings indicate that pending claims represent a recurrent process output arising from interdependent documentation practices, coding accuracy, and cross-unit coordination within the INA-CBG framework. The study concludes that strengthening internal verification, standardizing documentation and classification, and establishing routine monitoring indicators are essential to improve claim efficiency and organizational sustainability.